2020
DOI: 10.1590/1983-21252020v33n112rc
|View full text |Cite
|
Sign up to set email alerts
|

N:k Ratio for Phenological Growth Stages of Net Melon Cultivated in NFT Hydroponic System1

Abstract: The adequate ratio in the supply of nitrogen (N) and potassium (K) for each phenological growth stage of melon is fundamental for its growth and development with the maximization of the dry mass partition between the vegetative and reproductive parts. The objective of this study was to evaluate the influence of N and K concentrations in two phenological growth stages (vegetative and reproductive stage) of melon and obtain the best N:K ratio for each one. In the first stage, four concentrations of N (8, 11, 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…In a soil cultivation experiment, Oliveira et al (2020) did not observe a significant response from fruit quality traits. Nascimento et al (2020) described similar findings working with melon in hydroponics, where the K concentrations also did not affect the fruit size-related variables. In contrast, Gratieri et al (2013) analyzed the effect of N and K rates on melon grown in coconut fiber and found an increase in fruit weight as the K rates were increased, but the authors also noted that the K effect only occurred at high N rates.…”
Section: Fruit Yield Componentssupporting
confidence: 69%
See 1 more Smart Citation
“…In a soil cultivation experiment, Oliveira et al (2020) did not observe a significant response from fruit quality traits. Nascimento et al (2020) described similar findings working with melon in hydroponics, where the K concentrations also did not affect the fruit size-related variables. In contrast, Gratieri et al (2013) analyzed the effect of N and K rates on melon grown in coconut fiber and found an increase in fruit weight as the K rates were increased, but the authors also noted that the K effect only occurred at high N rates.…”
Section: Fruit Yield Componentssupporting
confidence: 69%
“…In the literature, studies investigating potassium fertilization in melon have described different results regarding qualitative traits (e.g. fruit size and weight) in response to an increase in the K rate in the soil or in hydroponic cultivation (Oliveira, Silva, Medeiros, & Vieira, 2020;Nascimento, Nascimento, & Cecílio, 2020;Gratieri, Cecílio, Barbosa, & Pavani, 2013). Studies can be found on the application of K as a salt stress-mitigating agent in crops such as peanut (Chakraborty, Bhaduri, Meena, & Kalariya, 2016), eggplant (Santos et al, 2018) and bell pepper (R. C. P. Silva et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…2020 http://dx.doi.org/ BJ-v36n0a2020-53595 in these treatments, which resulted in a reduction in the size and number of leaves, consequently reducing leaf area index and dry biomass accumulation. Colla, Suárez and Cardarelli (2010) and Nascimento, Nascimento and Cecílio Filho (2020) also found reduction of leaf area and dry biomass accumulation in melon plants under conditions of low N availability.…”
Section: Resultsmentioning
confidence: 85%
“…Every day it is checked to see if the seeds have sprouted (broken seeds) or not. The sign of shoots is the emergence of prospective roots (white-white) and the appearance of prospective leaves [5]. For 24 hours if the storage temperature is stable the seeds will germinate.…”
Section: Planting Seedsmentioning
confidence: 99%